2016
DOI: 10.1177/0961000616631613
|View full text |Cite
|
Sign up to set email alerts
|

The use of conversation-based programming in public libraries to support integration in increasingly multiethnic societies

Abstract: This paper theoretically explores how conversation-based programming in public libraries might support meaningful interactions between immigrants and individuals from the dominant ethnic group, and as a result, facilitate integration. The theoretical lens consists of Intergroup Contact Theory and a social-psychological model of integration. Four examples of library-based conversationbased programming are given in order to illustrate and expand upon the theoretical discussion: the Women's Story Circle at the Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…As public libraries have a strong mandate to serve the whole community through various inclusive practices [25], Alexander's civil sphere theory, with its heavy focus on solidarity, can be helpful when theorizing the democratic and inclusive mission of public libraries. Lacking in Alexander's theory is a focus on the public sphere as a place, as a physical location, an aspect that is captured by Habermas' theory, as well as other theories of public spheres, particularly those developed by Richard Sennett [26][27].…”
Section: Theories Of Public Spheresmentioning
confidence: 99%
“…As public libraries have a strong mandate to serve the whole community through various inclusive practices [25], Alexander's civil sphere theory, with its heavy focus on solidarity, can be helpful when theorizing the democratic and inclusive mission of public libraries. Lacking in Alexander's theory is a focus on the public sphere as a place, as a physical location, an aspect that is captured by Habermas' theory, as well as other theories of public spheres, particularly those developed by Richard Sennett [26][27].…”
Section: Theories Of Public Spheresmentioning
confidence: 99%
“…However, in a previous article by the author (Johnston, 2016b), it was argued that, though the research is promising, the existence of a language cafe or conversation circle does not guarantee the expansion of social networks across intercultural lines. Using Gordon Allport’s (1979) Contact Theory, the article proceeded to provide a firm theoretical basis for how conversation-based programming might support fruitful interactions between immigrants and community members – typically members of the majority – thus reducing divides in social networks that run along ethnic group lines.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the participants and volunteers break off into small groups and discuss the topic or theme. Programmes are generally informal and attended on a drop-in basis (Johnston, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study on a language cafe at Malmö City Library in Sweden found that the program supports language learning, expansion of social networks, as well as, information exchange relevant to economic and social integration, yet showed limited evidence for information exchange relevant to political integration. However, the study called for further research on the topic acknowledging that such programs might support political integration in other ways (Johnston, 2016a(Johnston, , 2016b.…”
Section: Introductionmentioning
confidence: 99%